Clean clothes a global movement to end sweatshops - Sluiter, Liesbeth; ebrary, Inc. (London ; New York : Pluto Press ; New York : Distributed in the U.S.A. by Palgrave Macmillan, 2009)
"The Clean Clothes Campaign is a worldwide movement that aims to improve the wages and conditions of sweatshop workers. This is the story of their struggle. Large retailers such as Tesco, Walmart and Carrefour lure shoppers in with prices that seem too good to be true. This book shows that they're too good to be fair. All along the industry's supply chain, workers, often children, are exploited through poverty wages, unpaid overtime and harsh anti-union measures. The campaign urges those in charge of the garment industry's supply lines to protect their workers and treat them fairly. This dynamic account of direct engagement by concerned consumers is a must read for those that see globalization differently and want their shopping choices to support the most vulnerable people involved in the clothing industry"--Publisher description.
pt. 1. A globalising industry -- pt. 2. A globalising network -- pt. 3. The campaign in action -- pt. 4. Debates and the future.
Includes bibliographical references (p. 293-294) and index.
Electronic reproduction.
Keywords: Sweatshops; Anti-sweatshop movement; Clothing trade -- Moral and ethical aspects; Clothing workers; Electronic books